The steroid-hormone ecdysone coordinates parallel pupariation neuromotor and morphogenetic subprograms via epidermis-to-neuron Dilp8-Lgr3 signal induction - Fabiana Heredia (Nature Portfolio, 2021)
Pupariation in Drosophila is triggered by the steroid-hormone ecdysone and requires coordination between associated behavioral and body-reshaping motor subprograms. The authors show that coordination requires ecdysone-dependent Dilp8-Lgr3 signaling between the cuticle epidermis and interneurons.